Implementation blues for the special Indian legislation to curb plagiarism in research in higher educational institutions - Khaire, Rupali; Dixit, Nalini; Ghuge, Ashok; Bhutada, Deepti; Kasisomayajula, Srinivasa Rao; Dhaigude, Rahul (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. In 2018, the Government of India implemented specific legislation through its primary agency, the University Grants Commission (UGC), with the objective of addressing issues of plagiarism in academic research. This legislation stipulated a systematic mechanism for higher educational institutions (HEIs) nationwide to ensure the academic integrity of research work. This paper examined the implementation status of the legislation after seven years since its announcement. Design/Methodology/Approach. A dual approach, incorporating both quantitative and qualitative methodologies, was employed in the study. A survey was conducted among 400 research supervisors with a minimum supervising experience of five years across the country. The survey utilized a questionnaire to assess the implementation level of the regulations. A Likert scale consisting of 10 Likert items was developed. The null hypothesis, which posited the implementation of the UGC Regulations 2018 as effective, was tested using a t-test. Subsequent to the survey results, 10 senior expert research supervisors were interviewed to ascertain how the implementation of the legislation could be improved. Results/Discussion. The findings of the study indicated that the awareness of the regulation among research scholars was limited. With the exception of plagiarism software, most statements on the scale received significant disagreement. Statements such as “researchers and supervisors are well aware of the objectives of the regulations,” “it is well understood that the regulations are binding on all the Higher Educational Institutions (HEIs),” “awareness programs are conducted regularly to disseminate information on academic integrity,” and “the establishment of Departmental and Institutional Academic Integrity Panels as mandated by the regulation has been done” received considerable disagreement among the 400 respondents. The expert group unanimously agreed that efforts to disseminate the legislation did not fully meet expectations. There was a significant need to take action to increase awareness of the regulation within the research community. It was important to implement software that aligned with the provisions of the Act. Conclusions. The necessity for legislation pertaining to plagiarism was generally recognized. The University Grants Commission (Promotion of Academic Integrity and Prevention of Plagiarism in Higher Educational Institutions) Regulations (2018) was a concise piece of legislation enacted by the Government of India. This legislation had received international attention, with other countries adopting similar measures. The government’s initiative in formulating a specialized law to address this issue was noteworthy. However, its implementation in HEIs had faced challenges. The enactment of the law and the provision of software for plagiarism detection had not yet led to substantial progress. The fundamental legislative objective of fostering awareness and cultivating acceptance of academic integrity had not been fully achieved, primarily due to insufficient awareness among students and research scholars regarding the provisions of the law.